Hak Ingkar Sebagai Alasan Pembenar Dihadapan Persidangan Pidana Bentuk Perlindungan Hukum Jabatan Notaris - Yudan Fajar Mahendra (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2024)
Notary is a public official who has the authority to make authentic deeds. Authentic deeds have formal functions that cannot be carried out by other public officials, so they have strong evidentiary power. In relation to this background, the author considers the following issues: the responsibility and legal protection of notaries for the deeds they make. The method used in this research is normative research using the technique of collecting legal materials through literature study, using primary and secondary legal materials. The results of the research show that the elements of the criminal act of falsifying an authentic deed committed by a notary include fulfilling subjective elements by falsifying an authentic deed. Criminal sanctions for notaries involved in this criminal act are based on Articles 264 paragraph (1) and 266 paragraph (1) of the Criminal Code, which stipulate penalties for notaries who make a deed by deliberately using the deed as if its contents were true. From this discussion, it can be concluded that deeds that do not meet the requirements set out in statutory regulations do not have strong evidentiary power and do not have binding legal force.